The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1302/2633-1462.29.bjo-2021-0079.r1
|View full text |Cite
|
Sign up to set email alerts
|

Waiting time for hip fracture surgery: hospital variation, causes, and effects on postoperative mortality

Abstract: Aims This study aimed to describe preoperative waiting times for surgery in hip fracture patients in Norway, and analyze factors affecting waiting time and potential negative consequences of prolonged waiting time. Methods Overall, 37,708 hip fractures in the Norwegian Hip Fracture Register from January 2014 to December 2018 were linked with data in the Norwegian Patient Registry. Hospitals treating hip fractures were characterized according to their hip fracture care. Waiting time (hours from admission to sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Possible explanations might be the selection of frail and high-risk patients to be treated by experienced surgeons, and the fact that patients treated with arthroplasty are preferentially operated on by more experienced surgeons and wait longer than other patients. 12 Orthogeriatric assessment is recommended to improve functional outcomes, 14 and has been shown to reduce mortality in FnFs receiving arthroplasty by roberts et al 22 in this study, orthogeriatric services were associated with lower mortality, all fracture types included. in a systematic review, abrahamsen et al 1 found that increased mortality might be elevated for years after injury, particularly for males.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Possible explanations might be the selection of frail and high-risk patients to be treated by experienced surgeons, and the fact that patients treated with arthroplasty are preferentially operated on by more experienced surgeons and wait longer than other patients. 12 Orthogeriatric assessment is recommended to improve functional outcomes, 14 and has been shown to reduce mortality in FnFs receiving arthroplasty by roberts et al 22 in this study, orthogeriatric services were associated with lower mortality, all fracture types included. in a systematic review, abrahamsen et al 1 found that increased mortality might be elevated for years after injury, particularly for males.…”
Section: Discussionmentioning
confidence: 60%
“…11 nPr also provided times of admission and procedures, which facilitated calculation of in-hospital waiting time for surgery, and identified patients treated with expedited surgery (within the day following admission). 12,13 Combining information on fracture type and treatment from the NHFR and waiting time from the NPR, we defined recommended surgical treatment within 48 hours of admission as best practice (according to national guidelines). 14 We collected demographic information (marital status and household type) and socioeconomic data (household income, highest completed education level, and residential status) from Statistics Norway (SN).…”
Section: Methodsmentioning
confidence: 99%
“…Many factors have been identified to affect the waiting time for surgeries among patients with hip fractures. This was supported by a retrospective analysis done in Norway [15]; although the mean preoperative waiting time was 22.6 hours, delayed surgeries were associated with increased 30-day and one-year mortality rates [15].…”
Section: Discussionmentioning
confidence: 88%
“…[5][6][7][8][16][17][18]20,[22][23][24][25][26] A large previous cohort study concluded that prolonged time to surgery was associated with higher 30-day and one-year mortality rates. 35 However, that study does not exclude patients who need preoperative optimization. 35 Thus, to optimize the more frail patients preoperatively more time would have been needed.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, that study does not exclude patients who need preoperative optimization. 35 Thus, to optimize the more frail patients preoperatively more time would have been needed. The results of that study do show this, as patients with longer time to surgery have higher CCI scores.…”
Section: Discussionmentioning
confidence: 99%